CASE REPORT: HIP DISSOCIATION AFTER CLOSED REDUCTION OF BIPOLAR HIP DISLOCATION - Lê Tuấn, Dũng; Mỵ Duy , Tiến; Lê Trung, Hiếu (Journal of 175 Practical Medicine and Pharmacy, 2023)
Bipolar hip dislocation after Bipolar hemiarthroplasty is uncommon complication with the rate between 1,2% - 2,4%. Closed reduction of dislocated bipolar hip joint can lead to dissociation of the components between the metal head and the polyethylene cup. The cause of the dissociation of hip implant after reduction is the “bottle opener” effect, when the polyethylen cup is locked by the posterior rim of the acetabulum. This rare complication lead to the need for reoperation. We report an 81-year-old female patient noticed dissociation of components of hip implant on X-ray after performing closed reduction of Bipolar hip dislocation.